GRETTA AND THE SPECTRAL: JOYCE, HUSTON AND THE LOGIC OF UNKNOWNNESS - Jukić, Tatjana (2008)
Joyce has survived for psychoanalysis and philosophy (Lacan, Deleuze, Derrida) where in psychoanalysis and philosophy he provokes archive fever, or rather still mal d'archive. Taking up "The Dead" as a narrative organized precisely around archive fever (or else around what always only emerges as the logic of unknownness), I propose to analyze it as an example of such survival, not least because examples— to quote from Derrida— always carry beyond themselves and thereby open up a testamentary dimension. Insofar as the archive fever in "The Dead" is provoked by the labor of the spectral and the visual— the kind of labor where the very promise of the cinematic seems to have survived the emergence of film— I cannot but also propose to see how this promise is kept where The Dead emerges as the testamentary film, by John Huston.